Hedonic Value and Performance Expectancy on Gen-Z’s Interest in Using the PayLater Application with Platform Trust Moderation - Widiya, Erlani; Priyastiwi, Priyastiwi (Research Horizon, 2026)
The rapid growth of digital financial services has made paylater applications popular among Generation Z, driven by both functional benefits and emotional trust, yet posing risks of consumptive behavior and financial problems. This study examines the influence of hedonic value and performance expectancy Generation Z’s interest in using paylater applications, with platform trust as a moderating variable. A quantitative approach was employed, targeting 155 respondents aged 18–27 in the Special Region of Yogyakarta, selected through purposive sampling. Data were collected via Likert-scale questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that performance expectancy positively and significantly influences interest in using paylater applications, while hedonic value does not show a significant effect. Moreover, trust in digital paylater platforms negatively moderates the effect of performance expectancy on user interest. These findings highlight that perceived functional benefits are the main driver of Generation Z’s adoption of paylater services, providing insights for digital finance providers to enhance user engagement responsibly. The study implies that providers should design paylater services that balance user convenience and enjoyment with mechanisms that promote responsible financial behavior.